The evolution of complex brains and behaviors in African cichlid fishes - Caroly A. Shumway (Current Zoology, 2010)
In this review, I explore the effects of both social organization and the physical environment, specifically habitat complexity, on the brains and behavior of highly visual African cichlid fishes, drawing on examples from primates and birds where appropriate. In closely related fishes from the monophyletic Ectodinii clade of Lake Tanganyika, both forces influence cichlid brains and behavior. Considering social influences first, visual acuity differs with respect to social organization (monogamy versus polygyny). Both the telencephalon and amygdalar homologue, area Dm, are larger in monogamous species. Monogamous species are found to have more vasotocin-immunoreactive cells in the preoptic area of the brain. Habitat complexity also influences brain and behavior in these fishes. Total brain size, telencephalic and cerebellar size are positively correlated with habitat complexity. Visual acuity and spatial memory are enhanced in cichlids living in more complex environments. However habitat complexity and social forces affect cichlid brains differently. Taken together, our field data and plasticity data suggest that some of the species-specific neural effects of habitat complexity could be the consequence of the corresponding social correlates. Environmental forces, however, exert a broader effect on brain structures than social ones do, suggesting allometric expansion of the brain structures in concert with brain size and/or co-evolution of these structures [Current Zoology 56 (1): 144–156 2010].